An evaluation of risk factors for infection with Coxiella burnetii in domestic goats. (October 2017) - Bauer, Amy E.; Johnson, April J.; Weng, Hsin-Yi; Pogranichniy, Roman M.; Moore, George E.
Highlights: Both serology and PCR were used to screen for C . burnetii infection. The presence of other hosts was negatively associated with C . burnetii infection. Transmission of C . burnetii between reservoir species needs investigation.